Hubungan Keterampilan Mengajar dengan Perilaku Belajar Menurut Peserta Didik di MDA Baitul Ikhlas Kecamatan Bayang Kabupaten Pesisir Selatan - Mila Marzona Muslim; Ismaniar Ismaniar (Universitas Negeri Padang, 2018)
The research was distributed by low level of behavioral learning learners in MDA Baitul Ikhlas Gurun Panjang Barat Village Bayang Sub-district Pesisir Selatan District. This is suspected because of poor teaching skills of educators. The type of this reseach is to description:1) describe the teaching skills of educators towards learners, (2) describe the behaviour of learners, and (3) to see whether there is a connection between the teacheng skills of educators with the learning behavior learners in MDA Baitul Ikhlas. Population in this research is 38 people. The technique use for taken sampling is Stratified random sampling as much as 80% of learners. The number of samples in this study was thirty students. Data collection techniques used were questionnaires, while data collection tools used questionnaires. Technique of data analysis by using formula of percentage and product moment. The result of research that is teaching skills which belonged to educators in the low category, behaviour of learners in the category is very low, and there is a significant correlation between the teaching skills of educators with learners learning behavior.Keywords: Teaching Skills, Learning Learners